Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0073886
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Cytological Analysis of a Novel Type of Low Temperature-Dependent Intrasubspecific Hybrid Weakness in Rice

Abstract: Hybrid weakness (HW) is an important postzygotic isolation which occurs in both intra- and inter-specific crosses. In this study, we described a novel low temperature-dependent intrasubspecific hybrid weakness in the F1 plants derived from the cross between two indica rice varieties Taifeng A and V1134. HW plants showed growth retardation, reduced panicle number and pale green leaves with chlorotic spots. Cytological assay showed that there were reduced cell numbers, larger intercellular spaces, thicker cell w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Segregation tests revealed that type II and type III necrosis are associated with a single genetic locus on the short arm of the D genome, chromosome 7D and 2D, respectively ( Mizuno et al 2010 , 2011 ). Temperature-dependent hybrid weakness is also observed in inter-specific hybrids in rice ( Chen et al 2014 , Fu et al 2013 ). One high-temperature dependent hybrid weakness is caused by the interaction between Hwi1 in wild rice, Oryza furipogon , and Hwi2 in indica rice, Oryza sativa ( Chen et al 2014 ).…”
Section: Molecular Evidence Of Reproductive Barriersmentioning
confidence: 92%
“…Segregation tests revealed that type II and type III necrosis are associated with a single genetic locus on the short arm of the D genome, chromosome 7D and 2D, respectively ( Mizuno et al 2010 , 2011 ). Temperature-dependent hybrid weakness is also observed in inter-specific hybrids in rice ( Chen et al 2014 , Fu et al 2013 ). One high-temperature dependent hybrid weakness is caused by the interaction between Hwi1 in wild rice, Oryza furipogon , and Hwi2 in indica rice, Oryza sativa ( Chen et al 2014 ).…”
Section: Molecular Evidence Of Reproductive Barriersmentioning
confidence: 92%
“…3. In addition to the crop-wild (interspecific) and indica – japonica (inter-subspecific) reproductive barriers, some barriers also exist between intra-subspecific hybridizations ( indica – indica and japonica – japonica ) ( Zhang 2012 ; Fu et al 2013 ). The hybrid weakness observed in the intra-subspecific hybridization ( indica – indica and japonica – japonica ) needs evolutionary as well as molecular analysis.…”
Section: Future Research Perspectivementioning
confidence: 99%
“…This conditionally expressed RI is also observed in plants. Most of the hybrid necrosis or weakness cases that have been studied so far are temperature sensitive ( Bomblies et al, 2007 ; Saito et al, 2007 ; Alcázar et al, 2009 ; Fu et al, 2013 ; Chen et al, 2014 ). Usually, low temperature promotes the expression of inferior symptoms.…”
Section: Environment and Hybrid Incompatibilitiesmentioning
confidence: 99%